Dynamic responses of concrete piers under close-in blast loading. (November 2016) - Hu, Zhi-Jian; Wu, Liang; Zhang, Yi-Feng; Sun, LZ
Piers are essential components for bridge structures while exposed directly to car-bombed detonation. Numerical simulation and failure-mode investigation are conducted for concrete piers under close-in blast loading to better understand their dynamic responses. The effects of pier geometry, reinforcement arrangement, and location of detonation are particularly studied on the horizontal velocity and displacement of the pier base. The results demonstrate that circular piers provide more effective blast resistance than square piers under the same blast circumstance. Failure modes for concrete piers are determined by the longitudinal rebar arrangement, which contributes to the major part of shear capacity of the pier base when subjected to close-in blast loading. While the hoop effect is limited for blast resistance of piers, the restraining influence of the ground is significant with respect to the pier base, and performance-based seismic design concept such as plastic-hinges can be employed at the base of concrete piers for anti-blast design.